Factors Affecting Perception Of Instructor In Using Learning Management System (LMS) - Al-Jeraifani, Fahad (2009)
This study aimed to investigate the instructors\' perceptions, barriers, and incentives toward the use of LMS as a tool for enhancing teaching and learning experience. The study investigated the demographic characteristics of faculty, their use of LMS, their purposes for using it, their perceptions about its educational/technical advantages and disadvantages, and their overall satisfaction as well as how their past experiences with the Internet and the computer toward the implementation of online instruction.